Satisfaction with Packaging and Price to Purchase Decision and Repurchase Intention - Indriani Putri Asmoro; Meylani Tuti (LPPM Universitas Negeri Jakarta, 2023)
Customers use their purchasing decision as a barometer when choosing items and as a catalyst for further purchases. This study set out to determine how packaging and pricing satisfaction affected consumers' decisions to buy and their willingness to do so again. With the use of smart PLS, this study analyzes structural equation models. 184 respondents were shoppers who made purchases in December 2022, as determined by the incidental sampling approach. The findings indicate that price satisfaction affects both the choice to buy and the desire to buy again. However, the packaging only influences the choice to buy and does not influence the urge to make more purchases. and the urge to make another buy is influenced by the outcome of the purchasing choice